Medial compartment cartilage repair and lower extremity biomechanical changes after single-plane high tibial osteotomy of distal tibial tuberosity. (June 2022) - Li, Xiaomin; Tan, Yetong; Tian, Xiangdong; Wang, Jian; Xue, Zhipeng; Ma, Sheng; Hu, Yuanyi; Ding, Tiansong; Wang, Jiajia; Zhao, Ze
Highlights: The medial compartment cartilage regeneration occurred after distal tibial tuberosity high tibial osteotomy (DTT-HTO), which laid a foundation for further research on cartilage regeneration. DTT-HTO can correct the biomechanical parameters of the knee joint and balance the pressure load between the medial and lateral compartments. DTT-HTO can effectively correct varus deformity, and relieve symptoms. The π-shaped plate can effectively prevent angle loss and internal fixation fractures due to its high levels of strength and stability. The discovery of cartilage regeneration and the change of stress load provide a basis for further research on knee biomechanics and delay the development of knee osteoarthritis. Abstract: Objective: To observe the cartilage repair of the medial compartment and the biomechanical changes of the lower extremities after single-plane high tibial osteotomy of distal tibial tuberosity (DTT-HTO). Methods: A total of 30 patients, including 11 males and 19 females, who underwent DTT-HTO with arthroscopic operation in our hospital from January 2020 to January 2021 and underwent arthroscopic exploration again during the second operation for internal fixation were enrolled. There were 32 knees, including 13 left knees and 19 right knees. Age ranged from 50 to 78, with an average of 63.20 ± 6.61 years old. All patients completed two surgeries and were followed up, and no adverse events occurred during the period. International Cartilage Repair Society (ICRS) was used to assess the cartilage condition of the medial compartment of the knee during the two surgeries. In this paper, the weight-bearing line ratio (WBLR), the medial proximal tibia angle (MPTA), the femoral tibial angle (FTA) and the posterior tibial slope (PTS) were used to evaluate the changes of the mechanical state of the lower limbs. The visual analogue scale (VAS) score and the Western Ontario and McMaster University Osteoarthritis (WOMAC) Index score were used to evaluate the improvement in knee pain and function. Results: All patients completed two operations without adverse events and serious complications. The medial compartment cartilage of all patients had different degrees of repair during the second operation, and the difference was statistically significant compared with the first operation ( P  < 0.05). During the second operation, the WBLR was corrected from (17.69 ± 2.16)% to (60.90 ± 1.97)%, the MPTA was corrected from (80.72 ± 1.61)° to (89.91 ± 2.58)°, the FTA was corrected from (182.31 ± 3.03)° to (171.81 ± 2.24)°, the difference was statistically significant ( P  < 0.05). There was no statistical difference in PTS between the two surgeries ( P >  0.05). At the second operation, the VAS score decreased from 7.50 ± 1.34 to 0.34 ± 0.85, the WOMAC score decreased from 119.50 ± 10.43 to 46.25 ± 4.13, and the difference was statistically significant ( P  < 0.05). Conclusion: DTT-HTO can significantly correct the weight-bearing line, restore the biomechanical parameters of the lower limb to the normal range, significantly relieve pain and improve knee function, and the medial compartment cartilage repair and regeneration phenomenon will occur after the correction of the weight-bearing line.